2019
DOI: 10.18535/jmscr/v7i1.99
|View full text |Cite
|
Sign up to set email alerts
|

Study of Coagulation Profile and Platelet Counts in Pre Eclamptic and Eclamptic Patients

Abstract: We conducted this prospective case-control study in rural population based medical institute of central India. The aim of the study was to assess and analyze the coagulation profile (PT, aPTT, fibrinogen and fibrin degradation product [FDP] levels) and platelet counts in 3 rd trimester normotensive, pre-eclamptic and eclamptic pregnant women. Methods: In all subjects (cases and controls) 2 ml of blood sample was collected in EDTA and tri-sodium citrate bulbs for platelet counts and coagulation profile respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…15 However, the extent of the coagulation problems caused by PE is unknown. Several studies have found that preeclamptic mothers have prolonged prothrombin time (PT) and activated partial thromboplastin time (APTT), [18][19][20][21][22] increased D-dimer levels, 8,17,20,23,24 and decreased levels of natural coagulation inhibitors: antithrombin III (ATIII), protein S (PS), and protein C (PC). [25][26][27][28][29] Despite the evidence of dysregulated coagulation parameters and natural anticoagulants in PE, the diagnostic potential of these parameters in predicting PE has not been explored among Ghanaian pregnant women which is a concerning limitation.…”
Section: Introductionmentioning
confidence: 99%
“…15 However, the extent of the coagulation problems caused by PE is unknown. Several studies have found that preeclamptic mothers have prolonged prothrombin time (PT) and activated partial thromboplastin time (APTT), [18][19][20][21][22] increased D-dimer levels, 8,17,20,23,24 and decreased levels of natural coagulation inhibitors: antithrombin III (ATIII), protein S (PS), and protein C (PC). [25][26][27][28][29] Despite the evidence of dysregulated coagulation parameters and natural anticoagulants in PE, the diagnostic potential of these parameters in predicting PE has not been explored among Ghanaian pregnant women which is a concerning limitation.…”
Section: Introductionmentioning
confidence: 99%